The Kajian Psikologi Keluarga: Benarkah Cinta adalah Unsur Terpenting dalam Pernikahan? - Rohmatul Hannani (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2023)
Love is the initial motivation for couples to decide to get married. However, love can change over the course of marriage. The pros and cons regarding the truth that love is the foundation and reason for the survival of a marriage need to be studied further. The importance of knowing the most important elements in marriage will minimize conflict and even divorce. The method used in this research is a descriptive qualitative method with data collection techniques based on literature studies. The study of marriage and all components of marriage is the object of this research. The main research data comes from the book "A Triangular Theory of Love" by Robert J. Sternberg and "The Seven Principles for Making Marriage Work" by John Gottman. Apart from that, supporting data such as books and articles related to marriage and studies of love in married life are also used as supporting references. The research results show the dynamics of changes in the type of love during marriage. There are three components to love including: (1) the intimacy component; (2) passion component; and (3) commitment component. These three components can form different types of love. The love component can increase and decrease and even disappear. However, the component of love that is a factor in a marriage lasting a long time is the component of commitment. This is because even if the passion and intimacy of a husband and wife change, if the marriage commitment is maintained firmly, the marriage will still be able to survive. The commitment component in love is the most important element in marriage which is the reason for the formation and survival of a marriage.